Tin-carbon composite material, preparation method thereof, pole piece and electrochemical device
By designing the tin-carbon composite material with cluster structure and graphene clad layer, the problem of poor circulation performance of existing tin-carbon materials is solved, and better electrochemical performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202411895737.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The electrochemical properties of existing tin carbon materials, especially poor circulation performance, limit their application in lithium-ion batteries.
By designing the cluster structure and graphene cladding, the single tin carbon composite particles have a core-shell structure, the core is porous tin oxide, the shell layer includes a first carbon layer and a second carbon layer in turn, and the conductive and mechanical properties are enhanced by the graphene cladding.
The electrochemical properties of tin-carbon composites are significantly improved, especially the cyclic properties, so that they can exhibit excellent performance at high current density.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a tin-carbon composite material and a preparation method thereof, a pole piece and an electrochemical device. Background Art
[0002] In recent years, the rapid development of electronic equipment and automobile fields, especially new energy vehicles, has led to a significant increase in the demand for lithium-ion batteries. This demand has put forward higher requirements for the high energy and high power density of the next generation of lithium-ion batteries, as well as the cycle performance at high current density. The theoretical capacity of the current mainstream negative electrode material graphite is only 372mAh / g, which cannot meet the higher requirements of the next generation of lithium-ion batteries. Therefore, new negative electrode materials with higher capacity are needed. At present, tin is considered to be one of the most promising alternative materials because of its high theoretical capacity of about 992mAh / g, which is 2-3 times that of graphite. However, tin will produce a huge volume expansion (>300%) during the charging and discharging process of lithium-ion batteries, which leads to a sharp decline in its capacity performance and cycle performance, thus limiting the application of this material. Therefore, researchers have also done a lot of work on the commercial application of this material: for example, the serious defect of tin's easy volume expansion can be effectively improved by compounding with carbon matrix materials (such as graphene, carbon nanotubes, and nanobelts); it can also be modified by modifying the tin body, such as preparing porous tin, tin nano, and three-dimensional structured tin.
[0003] Chinese patent application CN 116779825 A introduces a high-performance tin-carbon composite negative electrode material and its preparation method. First, the characteristic of sodium stannate trihydrate being hydrolyzed to form hydrated tin dioxide when dissolved in water is utilized, and ethanol is introduced to break the hydrolysis equilibrium, so that the reaction proceeds in the direction of increasing hydrated tin dioxide, and the hydrated tin dioxide gradually agglomerates into spheres to obtain tin oxide nanospheres; then the nanospheres are mixed and stirred with dopamine hydrochloride to polymerize to form coated tin oxide, which is then mixed and calcined with sulfur powder to obtain nitrogen-sulfur doped tin oxide, and finally the graphene oxide obtained by the improved Hummers method is wrapped on the surface of nitrogen-sulfur doped tin oxide to obtain a high-performance tin-carbon composite negative electrode material. However, the improvement of the cycle performance of the high-performance tin-carbon composite negative electrode material is still limited.
[0004] Therefore, it is urgent to propose a method to improve the cycle performance of tin-carbon materials, comprehensively enhance the performance of tin-carbon materials, and make them show excellent performance in cycle performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects of poor electrochemical performance, especially poor cycle performance, of the prior art tin-carbon materials, and provide a tin-carbon composite material and its preparation method, pole piece and electrochemical device. The tin-carbon composite material of the present invention has better electrical conductivity and lower charge transfer internal resistance. The battery assembled from the tin-carbon composite material has better electrochemical performance, especially better cycle performance. The preparation method of the tin-carbon composite material of the present invention is simple, highly practical and easy to industrialize.
[0006] The present invention solves the above technical problems through the following solutions.
[0007] The present invention provides a tin-carbon composite material, which comprises a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure comprises a plurality of tin-carbon composite particles, and second gaps are distributed between the tin-carbon composite particles;
[0008] Among them, a single tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, and a first gap is distributed between the first carbon layer and the second carbon layer.
[0009] In the present invention, the several means at least 2.
[0010] In the present invention, the D50 of the tin-carbon composite material may be 250-400 nm, preferably 280-370 nm, for example 365, 355, 350, 340, 330, 320 or 300 nm.
[0011] In the present invention, the tin content of the tin-carbon composite material may be 40%-60%, preferably 45%-55%, for example 51.9%, 51.3%, 51.2%, 51.1%, 50.9%, 50.7%, 50.6%, 50.3%, 50.1% or 49.9%.
[0012] In the present invention, the carbon content of the tin-carbon composite material may be 30%-50%, preferably 35%-45%, for example 40.94%, 40.2%, 40.85%, 40.51%, 40.31%, 40.24%, 40.07%, 39.99%, 39.97%, 39.89%, 39.87%, 39.79% or 39.26%.
[0013] In the present invention, the oxygen content of the tin-carbon composite material may be 5%-10%, preferably 6%-9%, for example 8.42%, 8.37%, 8.32%, 8.27%, 8.21%, 8.19%, 8.17%, 8.14%, 8.03%, 8.01%, 7.99%, 7.98%, 7.97% or 7.84%.
[0014] The content of each element mentioned above represents the percentage of the mass of each element to the mass of the tin-carbon composite material.
[0015] In the present invention, in the single tin-carbon composite particle, the first carbon layer preferably further comprises heteroatoms and / or tin-containing substances. Preferably, the first carbon layer further comprises heteroatoms and tin-containing substances.
[0016] The type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen.
[0017] The tin-containing substance is preferably a conventional tin-containing substance in the art, such as porous tin oxide.
[0018] Wherein, when the tin-containing substance is porous tin oxide, the porous tin oxide can be prepared by conventional methods in the art, preferably by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12.
[0019] The inorganic tin source may be of conventional type in the art, preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride.
[0020] Wherein, in the aqueous solution of the inorganic tin source, the molar volume ratio of the inorganic tin source to water may be (60-90) mmol:135 mL, for example, 75 mmol:135 mL.
[0021] Wherein, the type of the alkali is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium bicarbonate and sodium carbonate, such as sodium hydroxide. The alkali is generally added in the form of an alkaline solution. The molar concentration of the alkaline solution is preferably 1-3 mol / L, such as 2 mol / L.
[0022] Wherein, the molar ratio of the inorganic tin source to the base is preferably 1:(1.5-2.5), more preferably 1:(1.7-2.0), for example 1:1.8.
[0023] The reaction is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The reaction temperature may be 50-90° C., such as 60-80° C. The reaction time may be 40-60 min, such as 50 min.
[0024] Wherein, after the reaction, it is preferred to further include conventional washing and drying steps in the art. The washing preferably includes water washing and / or alcohol washing. The drying temperature may be 80-100°C.
[0025] In the present invention, in the single tin-carbon composite particle, the second carbon layer preferably further includes heteroatoms.
[0026] The type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen.
[0027] In the present invention, when the first carbon layer and / or the second carbon layer in the single tin-carbon composite particle include heteroatoms, the content of heteroatoms may be 0.2%-1.0%, preferably 0.6%-0.8%, such as 0.65%, 0.64%, 0.62%, 0.61%, 0.59%, 0.58%, 0.56%, 0.52%, 0.51% or 0.49%. The content of heteroatoms represents the percentage of the mass of heteroatoms to the mass of the tin-carbon composite material.
[0028] The present invention also provides a method for preparing a tin-carbon composite material, which comprises the following steps:
[0029] S1, performing a first carbon coating on porous tin oxide to obtain a first precursor;
[0030] S2, coating the first precursor with silicon dioxide to form a silicon dioxide layer to obtain a second precursor; mixing the aqueous dispersion of the second precursor with an oil phase solution containing an emulsifier, removing the solvent and performing heat treatment to obtain a third precursor;
[0031] S3, performing a second carbon coating on the third precursor, removing the silicon dioxide layer, and obtaining a fourth precursor;
[0032] S4, coating the fourth precursor with graphene to obtain a tin-carbon composite material.
[0033] In S1 of the present invention, the porous tin oxide can be prepared by conventional methods in the art, preferably by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12.
[0034] The inorganic tin source may be of conventional type in the art, preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride.
[0035] Wherein, in the aqueous solution of the inorganic tin source, the molar volume ratio of the inorganic tin source to water may be (73-84) mmol:135 mL, for example 75 mmol:135 mL.
[0036] Wherein, the type of the alkali is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium bicarbonate and sodium carbonate, such as sodium hydroxide. The alkali is generally added in the form of an alkaline solution. The molar concentration of the alkaline solution is preferably 1-3 mol / L, such as 2 mol / L.
[0037] Wherein, the molar ratio of the inorganic tin source to the base is preferably 1:(1.5-2.5), more preferably 1:(1.7-2.0), for example 1:1.8.
[0038] The reaction is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The reaction temperature may be 50-90° C., such as 60-80° C. The reaction time may be 40-60 min, such as 50 min.
[0039] After the reaction, the steps of filtering, washing and drying conventional in the art are preferably further included. The washing preferably includes water washing and / or alcohol washing. The drying temperature may be 80-100°C.
[0040] In S1 of the present invention, the temperature of the first carbon coating may be 550-850° C., such as 650, 700 or 750° C. The time of the first carbon coating may be 6-15 hours, such as 8, 10 or 12 hours.
[0041] In S1 of the present invention, the type of carbon source for the first carbon coating can be conventional in the art, preferably phenolic resin and / or asphalt, such as phenolic resin fixed by a surfactant.
[0042] Among them, when the type of the carbon source is phenolic resin, the preparation method of the porous tin oxide for the first carbon coating preferably includes the following steps: mixing resorcinol, formaldehyde, a catalyst and porous tin oxide, polymerization reaction and the first carbon coating.
[0043] The molar ratio of the formaldehyde to the resorcinol may be (500-1000): (0.5-1.0), for example, 1000: 1. The catalyst may be a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate. The molar ratio of the resorcinol to the catalyst may be (0.5-1.0): (0.007-0.03), for example, 0.6: 0.01. The molar ratio of the resorcinol to the porous tin oxide is preferably (0.5-1.0): (2-3), for example, 0.6: 3 or 0.6: 2.5. The temperature of the polymerization reaction may be 80-100° C., for example, 90° C. The time of the polymerization reaction may be 2-10 h, for example, 8 h. After the polymerization reaction and before the first carbon coating, a drying step is preferably further included. Wherein, the drying operation may be conventional in the art, such as freeze drying, supercritical drying or vacuum drying. The freeze drying temperature may be -30 to -80° C., for example, -60° C. The freeze drying time may be 3-7h, for example 4h. The supercritical drying temperature may be 10-40°C, for example 20 or 30°C. The supercritical drying time may be 1-3h, for example 1.5 or 2h. During the supercritical drying, the pressure of the system may be 10-15kPa, for example 10kPa. The vacuum drying temperature may be 80-100°C, for example 90°C. The vacuum drying time may be 10-20h, for example 15h.
[0044] Among them, when the type of the carbon source is a phenolic resin fixed with a surfactant, the preparation method of the porous tin oxide for the first carbon coating preferably includes the following steps: mixing an aqueous solution of the surfactant, resorcinol, formaldehyde, a catalyst and porous tin oxide, polymerization reaction and the first carbon coating.
[0045] The type of the surfactant is preferably one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, cetyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, for example cetyltrimethylammonium bromide.
[0046] In the aqueous solution of the surfactant, the molar ratio of the surfactant to the water is preferably (0.3-0.65):(4000-10000), for example 0.45:6000.
[0047] The molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.0), for example 0.45:0.6.
[0048] In S1 of the present invention, the carbon source during the first carbon coating is preferably further added with heteroatoms and / or tin-containing substances.
[0049] Among them, when heteroatoms are added to the carbon source during the first carbon coating, the method for preparing the porous tin oxide for the first carbon coating preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and porous tin oxide, polymerization reaction and the first carbon coating.
[0050] The type of the heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the type of the heteroatom is nitrogen, the type of the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as triethylamine.
[0051] The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.0), for example 0.04:0.6.
[0052] Among them, when a tin-containing substance is also added to the carbon source during the first carbon coating, the preparation method of the porous tin oxide for the first carbon coating preferably includes the following steps: mixing an aqueous solution including a surfactant and a tin-containing substance, resorcinol, formaldehyde, a catalyst and porous tin oxide, polymerization reaction and the first carbon coating.
[0053] The type of the surfactant is preferably one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as cetyltrimethylammonium bromide.
[0054] The tin-containing substance is preferably a conventional tin-containing substance in the art, such as porous tin oxide.
[0055] When the tin-containing substance is porous tin oxide, the porous tin oxide can be prepared by conventional methods in the art, preferably by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12.
[0056] The inorganic tin source may be any conventional source in the art, and is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride.
[0057] In the aqueous solution of the inorganic tin source, the molar volume ratio of the inorganic tin source to water may be (60-90) mmol:135 mL, for example 75 mmol:135 mL.
[0058] The type of the alkali is preferably one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium bicarbonate and sodium carbonate, such as sodium hydroxide. The alkali is generally added in the form of an alkaline solution. The molar concentration of the alkaline solution is preferably 1-3 mol / L, such as 2 mol / L.
[0059] The molar ratio of the inorganic tin source to the base is preferably 1:(1.5-2.5), more preferably 1:(1.7-2.0), for example 1:1.8.
[0060] The reaction is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen. The reaction temperature may be 50-90° C., such as 60-80° C. The reaction time may be 40-60 min, such as 50 min.
[0061] After the reaction, the steps of washing and drying conventional in the art are preferably further included. The washing preferably includes water washing and / or alcohol washing. The drying temperature may be 80-100°C.
[0062] The molar ratio of the surfactant to the tin-containing substance is preferably (0.3-0.65):(0.5-1.0) g, such as 0.45:0.5 or 0.45:0.8.
[0063] In the aqueous solution of the surfactant and the tin-containing substance, the molar ratio of the surfactant to water is preferably (0.3-0.65):6000, such as 0.45:6000.
[0064] The molar ratio of the tin-containing substance to the porous tin oxide is preferably (0.5-1.0):(2-3), for example 0.8:3, 0.5:3 or 0.8:2.5.
[0065] Among them, when heteroatoms and tin-containing substances are also added to the carbon source during the first carbon coating, the method for preparing the porous tin oxide for the first carbon coating preferably includes the following steps: mixing an aqueous solution including a surfactant and a tin-containing substance with a heteroatom source, resorcinol, formaldehyde, a catalyst and porous tin oxide, polymerization reaction and the first carbon coating.
[0066] In S1 of the present invention, the structure of the first precursor may be porous tin oxide and a first carbon layer coated on the porous tin oxide.
[0067] In S1 of the present invention, preferably, the structure of the first precursor is porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer further includes heteroatoms and / or tin-containing substances.
[0068] In S2 of the present invention, the method for preparing the first precursor by coating it with silicon dioxide preferably comprises the following steps: mixing the first precursor, a silicon source and an ammonia solution, acid washing, and heat treatment.
[0069] The type of silicon source can be conventional in the art, preferably silicate or silicate. The silicate is preferably ethyl orthosilicate and / or methyl orthosilicate. The silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate.
[0070] The mass percentage of ammonia in the ammonia solution is preferably 25%-30%, for example 28%.
[0071] The mass volume ratio of the first precursor to the silicon source is preferably (2-5) g: (3-10) mL, for example 4 g: 8 mL or 5 g: 6 mL.
[0072] The mass ratio of the first precursor to the volume ratio of the ammonia is preferably (6-10) g:70 mL, for example 4 g:70 mL.
[0073] The mixing time is preferably 40-60 min, such as 50 min.
[0074] The acid used for pickling can be a conventional inorganic acid in the art, such as hydrochloric acid. The pickling generally uses an aqueous solution of an acid, such as an aqueous solution of an acid with a molar concentration of 2M.
[0075] After the acid washing and before the heat treatment, it is preferred to further include conventional steps of filtration, washing and drying in the art.
[0076] The temperature of the heat treatment is preferably 600-800° C., such as 600 or 650° C. The time of the heat treatment is preferably 6-10 h, such as 8 h. The rate of heating from room temperature to the temperature of the heat treatment is preferably 1-10° C. / min, such as 3° C. / min.
[0077] In S2 of the present invention, the structure of the second precursor may include a first precursor and a silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coating the porous tin oxide.
[0078] In S2 of the present invention, preferably, the structure of the second precursor may include a first precursor and a silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes heteroatoms and / or tin-containing substances.
[0079] In the present invention S2, the aqueous dispersion of the second precursor preferably comprises the second precursor, a surfactant and water.
[0080] The surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide.
[0081] The ratio of the second precursor, the surfactant and the water is preferably (3-5) g: (0.3-0.5) mol: 300 mL, for example 4 g: 0.45 mol: 300 mL.
[0082] In S2 of the present invention, the type of the emulsifier may be an emulsifier having a hydrophile-lipophile balance (HLB) of 3-8, preferably an emulsifier having a hydrophile-lipophile balance (HLB) of 4-7, and more preferably one or more of propylene glycol fatty acid esters, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate.
[0083] In S2 of the present invention, the type of the oil phase solvent in the oil phase solution containing the emulsifier can be conventional in the art, and is preferably an olefin having 12 to 28 carbon atoms, such as 1-octadecene.
[0084] In S2 of the present invention, the mass percentage of the emulsifier in the oil phase solution containing the emulsifier may be 0.3-0.8wt%, preferably 0.4-0.7wt%, for example 0.6wt%.
[0085] In S2 of the present invention, the mass ratio of the second precursor to the emulsifier may be 4:(0.9-2.4), for example, 4:1.8.
[0086] In S2 of the present invention, the method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 95-98°C.
[0087] In S2 of the present invention, the temperature of the heat treatment is preferably 450-600° C., such as 550° C. The time of the heat treatment is preferably 0.5-1.5 h, such as 1 h. The heat treatment is preferably performed in an air atmosphere.
[0088] In S2 of the present invention, the heat treatment preferably further includes a condensation step.
[0089] In S2 of the present invention, the structure of the third precursor may include a second precursor distributed in a cluster structure; the structure of the second precursor includes a first precursor and a silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide.
[0090] In S2 of the present invention, preferably, the structure of the third precursor may include a second precursor distributed in a cluster structure; the structure of the second precursor includes a first precursor and a silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes heteroatoms and / or tin-containing substances.
[0091] In S3 of the present invention, the temperature of the second carbon coating may be 500-900° C., such as 700 or 750° C. The time of the second carbon coating may be 8-24 hours, such as 15 hours.
[0092] In S3 of the present invention, the type of carbon source for the second carbon coating can be conventional in the art, preferably phenolic resin and / or asphalt, such as phenolic resin fixed by a surfactant.
[0093] Wherein, when the type of the carbon source is phenolic resin, the method for preparing the third precursor by subjecting it to a second carbon coating preferably comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the third precursor, polymerizing and subjecting it to a second carbon coating.
[0094] The molar ratio of the formaldehyde to the resorcinol may be (500-1000): (0.5-1.0), for example, 1000: 1 or 1600: 1. The catalyst may be a base, preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate. The molar ratio of the resorcinol to the catalyst may be (0.5-1.0): (0.007-0.03), for example, 0.8: 0.01 or 0.5: 0.01. The molar mass ratio of the resorcinol to the third precursor is preferably (0.5-1.0) mmol: (2-4) g, for example, 0.8 mmol: 3.5 g, 0.5 mmol: 3.5 g or 0.8 mmol: 4.0 g. The temperature of the polymerization reaction may be 80-100° C., for example, 90° C. The time of the polymerization reaction may be 2-10 h, for example, 8 h. After the polymerization reaction and before the first carbon coating, a drying step is preferably further included. Wherein, the drying operation may be conventional in the art, such as freeze drying, supercritical drying or vacuum drying. The freeze drying temperature may be -30 to -80°C, for example -60°C. The freeze drying time may be 3-7h, for example 4h. The supercritical drying temperature may be 10-40°C, for example 20 or 30°C. The supercritical drying time may be 1-3h, for example 1.5 or 2h. During the supercritical drying, the pressure of the system may be 10-15kPa, for example 10kPa. The vacuum drying temperature may be 80-100°C, for example 90°C. The vacuum drying time may be 10-20h, for example 15h.
[0095] Among them, when the type of the carbon source is a phenolic resin fixed with a surfactant, the preparation method of the third precursor for a second carbon coating preferably includes the following steps: mixing an aqueous solution of a surfactant, resorcinol, formaldehyde, a catalyst and a third precursor, polymerization reaction and second carbon coating.
[0096] The type of the surfactant is preferably one or more of cetyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide, such as cetyltrimethylammonium bromide.
[0097] In the aqueous solution of the surfactant, the molar ratio of the surfactant to the water is preferably (0.3-0.65):(8000-12000), for example 0.55:10000 or 0.45:10000.
[0098] The molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.0), such as 0.55:0.8 or 0.45:0.8.
[0099] In S3 of the present invention, the carbon source is preferably further added with heteroatoms during the second carbon coating.
[0100] Among them, when heteroatoms are added to the carbon source during the second carbon coating, the method for preparing the third precursor for the second carbon coating preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the third precursor, polymerization reaction and second carbon coating.
[0101] The type of the heteroatom may be one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen. When the type of the heteroatom is nitrogen, the type of the nitrogen source may be a nitrogen-containing substance, preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as triethylamine.
[0102] The molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.0), for example 0.03:0.8 or 0.03:0.5.
[0103] In S3 of the present invention, the method for removing the silicon dioxide layer may be etching. The etching solution used for the etching is preferably a hydrofluoric acid solution. The mass percentage of hydrofluoric acid in the hydrofluoric acid solution is preferably 4-6wt%, such as 5wt%.
[0104] In S3 of the present invention, the structure of the fourth precursor may include a cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, and a first void is distributed between the first carbon layer and the second carbon layer.
[0105] In S3 of the present invention, preferably, the structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, and a first void is distributed between the first carbon layer and the second carbon layer, and the first carbon layer also includes heteroatoms and / or tin-containing substances.
[0106] In S3 of the present invention, preferably, the structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first void is distributed between the first carbon layer and the second carbon layer, and the second carbon layer also includes heteroatoms.
[0107] In S3 of the present invention, preferably, the structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first void is distributed between the first carbon layer and the second carbon layer, the first carbon layer also includes heteroatoms and / or tin-containing substances, and the second carbon layer also includes heteroatoms.
[0108] In S4 of the present invention, the carbon source used for the graphene carbon coating may be a conventional carbon source in the art that can form graphene or graphene oxide, preferably humic acid.
[0109] Among them, when the carbon source is humic acid, the graphene carbon coating is preferably performed by first mixing the fourth precursor, humic acid and water, and then dropping an ammonia solution under stirring conditions to remove the solvent.
[0110] The amount of water used is not limited, so that the solid-liquid ratio in the mixed solution of the fourth precursor, humic acid and water is preferably 1:(10-15), for example 1:12.
[0111] The ammonia content in the aqueous ammonia solution is preferably 25%-30%, for example 28%. The amount of the aqueous ammonia solution used is not limited, as long as the humic acid powder is completely dissolved.
[0112] The method for removing the solvent may be conventional in the art, such as evaporation. The temperature during the evaporation may be 80-100°C, such as 90°C.
[0113] In S4 of the present invention, the mass ratio of the fourth precursor to the carbon source during the carbon coating of the graphene may be 100:(10-20), preferably 100:(11-18), for example 100:15 or 100:12.
[0114] In S4 of the present invention, the graphene carbon coating is preferably subjected to a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering.
[0115] The temperature of the first sintering step is preferably 200-350°C, such as 260 or 300°C. The time of the first sintering step is preferably 5-15h, such as 10h. The first sintering step is preferably performed in a microwave oven. The power of the microwave oven can be 800-1100W, such as 1000W.
[0116] The end point of the cooling may be room temperature, generally 20-30°C.
[0117] The temperature of the second stage sintering is preferably 500-800°C, such as 600 or 700°C. The time of the second stage sintering is preferably 10-24h, such as 18h. The rate of heating from room temperature to the temperature of the second stage sintering can be 1-10°C / min, such as 3°C / min. The second stage sintering is preferably carried out in a tubular furnace. The second stage sintering is preferably carried out under an inert atmosphere. The inert atmosphere is preferably nitrogen.
[0118] In S4 of the present invention, the structure of the tin-carbon composite material may include a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second gaps are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell layer coating the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, and a first gap is distributed between the first carbon layer and the second carbon layer.
[0119] In S4 of the present invention, preferably, the structure of the tin-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell coating the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first void is distributed between the first carbon layer and the second carbon layer, and the first carbon layer also includes heteroatoms and / or tin-containing substances.
[0120] In S4 of the present invention, preferably, the structure of the tin-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell coating the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first void is distributed between the first carbon layer and the second carbon layer, and the second carbon layer also includes heteroatoms.
[0121] In S4 of the present invention, preferably, the structure of the tin-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell coating the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first void is distributed between the first carbon layer and the second carbon layer, the first carbon layer also includes heteroatoms and / or tin-containing substances, and the second carbon layer also includes heteroatoms.
[0122] The present invention provides a silicon-tin-carbon composite material, which is prepared by the preparation method of the silicon-tin composite material as mentioned above.
[0123] The present invention also provides a pole piece, which comprises the silicon-tin-carbon composite material as described above.
[0124] The present invention also provides an electrochemical device, which comprises the pole piece as described above.
[0125] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0126] The reagents and raw materials used in the present invention are commercially available.
[0127] The positive and progressive effects of the present invention are:
[0128] (1) The tin-carbon composite material prepared by the present invention includes a cluster structure and a graphene layer coated on the cluster structure, wherein the cluster structure includes a plurality of tin-carbon composite particles; a single tin-carbon composite particle includes a porous tin oxide, a first carbon layer and a second carbon layer in sequence from the inner core to the direction away from the inner core, and the design of the porous structure and the multi-layer carbon layer provides space for the expansion of tin oxide, which can effectively alleviate the volume expansion of tin oxide; gaps are distributed between the cluster structures, which sets a second line of defense for the volume expansion of tin oxide; further, the graphene coating layer has good electrical conductivity and mechanical properties, which provides another line of defense for the volume expansion of tin oxide, and can make the tin-carbon composite material have good electrochemical properties.
[0129] (2) The battery assembled from the tin-carbon composite material has better electrochemical performance, especially better cycle performance.
[0130] (3) The preparation method of the tin-carbon composite material of the present invention is simple, does not require the involvement of a large amount of chemical reagents, is highly practical, can be operated on a large scale, and is easy to industrialize. DETAILED DESCRIPTION
[0131] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0132] Example 1
[0133] S1. Preparation of the first precursor:
[0134] (1) Mix stannous chloride (75 mmol) and deionized water (135 mL) and stir for 40 min until the stannous chloride is completely dissolved. After sufficient stirring, add 2 mol / L sodium hydroxide solution (prepared using 67.5 mL deionized water) dropwise into the above stannous chloride aqueous solution. Under a nitrogen atmosphere, continue the reaction at 60-80 ° C for 50 min, and maintain the pH value of the system at 5-12 (the molar ratio of stannous chloride to sodium hydroxide is 1:1.8). Filter the obtained precipitate and then rinse it repeatedly with water and ethanol respectively. Then dry it under vacuum at 80-100 ° C overnight to obtain porous tin dioxide.
[0135] (2) Hexadecyltrimethylammonium bromide (0.45 mmol) and 0.8 mmol of the porous tin dioxide prepared in step (1) are mixed, and ultrasonically dispersed so that the mixture is evenly distributed in deionized water (6 mol) to form spherical micelles, on which the porous tin dioxide is fixed.
[0136] (3) Add triethylamine (0.04 mmol), resorcinol (0.6 mmol), formaldehyde (0.6 mol) and sodium carbonate (0.01 mmol) to the mixture prepared in step (2), and continue stirring to obtain a surface-stabilized sol. Subsequently, add 3 mmol of the porous tin dioxide prepared in step (1) and disperse evenly. Then polymerize at 90°C for 8 hours, and then vacuum dry at 90°C for 18 hours, and then first carbon coat at 700°C for 10 hours under a nitrogen atmosphere. Then rinse repeatedly with water and ethanol, respectively, and vacuum dry at 90°C for 15 hours to obtain a first precursor. The structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0137] S2. Preparation of the second precursor: (1) 8 mL of tetraethyl orthosilicate and 4 g of the first precursor were added to 250 mL of 28% ammonia solution in sequence, mixed and stirred for 50 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 650 ° C, the heating rate was 3 ° C / min, and the silicon dioxide layer was fixed for 8 h to obtain the second precursor. The structure of the second precursor includes the first precursor and the silicon dioxide layer covering the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer covering the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0138] Preparation of the third precursor: (2) 4 g of the second precursor prepared in step (1) is uniformly dispersed in 300 mL of deionized water containing 0.45 mol of a surfactant (hexadecyltrimethylammonium bromide) to form an aqueous dispersion, and mixed with 300 mL of a 1-octadecene solution containing 0.6 wt% of diethylene glycol monooleate to form an oil-in-water emulsion. After evaporating the solvent at 95-98°C, the mixture is collected by centrifugation and then heat-treated at 550°C for 1 h in an air atmosphere to remove organic matter, followed by condensation to obtain the third precursor. The structure of the third precursor includes a second precursor distributed in a clustered structure; the structure of the second precursor includes a first precursor and a silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coating the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0139] S3, preparation of the fourth precursor: 0.55mmol surfactant (hexadecyltrimethylammonium bromide) and 10mol deionized water were mixed and ultrasonically dispersed for 50min to form spherical micelles. Then triethylamine (0.03mmol), resorcinol (0.8mmol), formaldehyde (0.8mol) and sodium carbonate (0.01mmol) were added and stirred continuously. Subsequently, 3.5g of the third precursor obtained in step S2 (2) was added. Then, polymerization was carried out at 90℃ for 10h, and then vacuum dried at 90℃ for 18h, and then the second carbon coating was carried out at 750℃ for 15h under nitrogen atmosphere. Finally, the silicon dioxide layer was removed with 5wt% HF solution to obtain the fourth precursor. The structure of the fourth precursor includes a cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second voids are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, and a first void is distributed between the first carbon layer and the second carbon layer, and the first carbon layer also includes nitrogen doping and porous tin oxide, and the second carbon layer also includes nitrogen doping.
[0140] S4, the fourth precursor prepared in step S3 is mixed with humic acid (model 53680-10G, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) at a mass ratio of 100:15, and added into deionized water for uniform mixing, the solid-liquid ratio is controlled at 1:12, and then a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved, and then heated to 90°C and the solvent is evaporated to make the humic acid uniformly coated on the surface of the fourth precursor; and sintered at 300°C for 10h in a microwave oven (microwave power of 1000W), cooled to room temperature, taken out, and then placed in a tubular furnace under an inert atmosphere at a rate of 3°C / min from room temperature to 700°C for 18h, so that the humic acid is thermally decomposed and graphene is synthesized in situ to obtain a tin-carbon composite material. The structure of the tin-carbon composite material includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second gaps are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with a core and a shell coating the core; wherein the core includes porous tin oxide; the shell includes a first carbon layer and a second carbon layer in sequence along a direction away from the core, a first gap is distributed between the first carbon layer and the second carbon layer, the first carbon layer also includes nitrogen doping and porous tin oxide, and the second carbon layer also includes nitrogen doping.
[0141] Example 2
[0142] The difference from Example 1 is that 0.5 mmol of porous tin dioxide is added in step S1 (2).
[0143] Example 3
[0144] The difference from Example 1 is that 2.5 mmol of porous tin dioxide is added in step S1 (3).
[0145] Example 4
[0146] The difference from Example 1 is that the temperature of the first carbon coating in step S1 (3) is 650°C.
[0147] Example 5
[0148] The difference from Example 1 is that the silicon source in step S2 (1) is methyl orthosilicate.
[0149] Example 6
[0150] The difference from Example 1 is that the heat treatment temperature in step S2 (1) is 600°C.
[0151] Example 7
[0152] The difference from Example 1 is that in step S2 (2), a 0.8 wt % diethylene glycol monooleate 1-octadecene solution is used.
[0153] Example 8
[0154] The difference from Example 1 is that the emulsifier in step S2 (2) is glyceryl monostearate.
[0155] Example 9
[0156] The difference from Example 1 is that the surfactant in step S3 is 0.45 mmol.
[0157] Example 10
[0158] The difference from Example 1 is that 0.5 mmol of resorcinol is added in step S3.
[0159] Embodiment 11
[0160] The difference from Example 1 is that 4 g of the third precursor is added in step S3.
[0161] Example 12
[0162] The difference from Example 1 is that the temperature of the second carbon coating in step S3 is 700°C.
[0163] Example 13
[0164] The difference from Example 1 is that in step S4, the mass ratio of the fourth precursor prepared in step S3 to humic acid is 100:12.
[0165] Embodiment 14
[0166] The difference from Example 1 is that the temperature of the first sintering in step S4 is 260°C.
[0167] Embodiment 15
[0168] The difference from Example 1 is that the temperature of the second stage sintering in step S4 is 600°C.
[0169] Comparative Example 1
[0170] The difference from Example 1 is that the negative electrode material is pure tin powder.
[0171] Comparative Example 2
[0172] The difference from Example 1 is that the negative electrode material is pure graphene.
[0173] Comparative Example 3
[0174] S1. Preparation of the first precursor:
[0175] (1) Mix stannous chloride (75 mmol) and deionized water (135 mL) and stir for 40 min until the stannous chloride is completely dissolved. After sufficient stirring, add 2 mol / L sodium hydroxide solution (prepared using 67.5 mL deionized water) dropwise into the above aqueous solution of stannous chloride. Under a nitrogen atmosphere, continue the reaction at 60-80 ° C for 50 min, and maintain the pH value of the system at 5-12. Filter the obtained precipitate and then rinse it repeatedly with water and ethanol. Then dry it under vacuum at 80-100 ° C overnight to obtain porous tin dioxide.
[0176] (2) Hexadecyltrimethylammonium bromide (0.45 mmol) and 0.8 mmol of the porous tin dioxide prepared in step (1) are mixed, and ultrasonically dispersed so that the mixture is evenly distributed in deionized water (6 mol) to form spherical micelles, on which the porous tin dioxide is fixed.
[0177] (3) Add triethylamine (0.04 mmol), resorcinol (0.6 mmol), formaldehyde (0.6 mol) and sodium carbonate (0.01 mmol) to the mixture prepared in step (2), and continue stirring to obtain a surface-stabilized sol. Subsequently, add 3 mmol of the porous tin dioxide prepared in step (1) and disperse evenly. Then polymerize at 90°C for 8 hours, and then vacuum dry at 90°C for 18 hours, and then first carbon coat at 700°C for 10 hours under a nitrogen atmosphere. Then rinse repeatedly with water and ethanol, respectively, and vacuum dry at 90°C for 15 hours to obtain a first precursor. The structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0178] S2. Preparation of the second precursor: 8 mL of tetraethyl orthosilicate and 4 g of the first precursor are added to 250 mL of ammonia solution with a mass concentration of 28%, mixed and stirred for 50 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 650 ° C, the heating rate is 3 ° C / min, and the silicon dioxide layer is fixed by heat treatment for 8 h to obtain the second precursor. The structure of the second precursor includes the first precursor and the silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0179] S3, preparation of the third precursor: the second precursor prepared in step S2 is mixed with humic acid in a mass ratio of 100:15, and added into deionized water and mixed evenly, the solid-liquid ratio is controlled at 1:12, and then a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved, and then heated to 90°C and the solvent is evaporated to make the humic acid evenly coated on the surface of the second precursor; and sintered at 300°C for 10h in a microwave oven (microwave power of 1000W), cooled to room temperature, and then placed in a tubular furnace under an inert atmosphere at a rate of 3°C / min from room temperature to 700°C for 18h, so that the humic acid is thermally decomposed and graphene is synthesized in situ; the silicon dioxide layer is removed with a 5 wt% HF solution to obtain a tin-carbon composite material. The structure of the tin-carbon composite material includes tin-carbon composite particles and a graphene layer coated on the tin-carbon composite particles; the tin-carbon composite particles include porous tin oxide and a first carbon layer coated on the surface of the porous tin oxide, the first carbon layer also includes nitrogen-doped and porous tin oxide, and gaps are distributed between the first carbon layer and the graphene layer.
[0180] Comparative Example 4
[0181] The difference from Example 1 is that no cluster structure is prepared, specifically:
[0182] S1. Preparation of the first precursor:
[0183] (1) Mix stannous chloride (75 mmol) and deionized water (135 mL) and stir for 40 min until the stannous chloride is completely dissolved. After sufficient stirring, add 2 mol / L sodium hydroxide solution (prepared using 67.5 mL deionized water) dropwise into the above aqueous solution of stannous chloride. Under a nitrogen atmosphere, continue the reaction at 60-80 ° C for 50 min, and maintain the pH value of the system at 5-12. Filter the obtained precipitate and then rinse it repeatedly with water and ethanol. Then dry it under vacuum at 80-100 ° C overnight to obtain porous tin dioxide.
[0184] (2) Hexadecyltrimethylammonium bromide (0.45 mmol) and 0.8 mmol of the porous tin dioxide prepared in step (1) are mixed, and ultrasonically dispersed so that the mixture is evenly distributed in deionized water (6 mol) to form spherical micelles, on which the porous tin dioxide is fixed.
[0185] (3) Add triethylamine (0.04 mmol), resorcinol (0.6 mmol), formaldehyde (0.6 mol) and sodium carbonate (0.01 mmol) to the mixture prepared in step (2), and continue stirring to obtain a surface-stabilized sol. Subsequently, add 3 mmol of the porous tin dioxide prepared in step (1) and disperse evenly. Then polymerize at 90°C for 8 hours, and then vacuum dry at 90°C for 18 hours, and then first carbon coat at 700°C for 10 hours under a nitrogen atmosphere. Then rinse repeatedly with water and ethanol, respectively, and vacuum dry at 90°C for 15 hours to obtain a first precursor. The structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0186] S2. Preparation of the second precursor: 8 mL of tetraethyl orthosilicate and 4 g of the first precursor are added to 250 mL of ammonia solution with a mass concentration of 28%, mixed and stirred for 50 min, filtered and cleaned, and pickled with 2 mol / L hydrochloric acid, filtered and cleaned again, and dried; then, at 650 ° C, the heating rate is 3 ° C / min, and the silicon dioxide layer is fixed by heat treatment for 8 h to obtain the second precursor. The structure of the second precursor includes the first precursor and the silicon dioxide layer coating the first precursor; the structure of the first precursor includes porous tin oxide and a first carbon layer coated on the porous tin oxide, and the first carbon layer also includes nitrogen doping and porous tin oxide.
[0187] S3, preparation of the third precursor: 0.55mmol surfactant (hexadecyltrimethylammonium bromide) and 10mol deionized water were mixed and ultrasonically dispersed for 50min to form spherical micelles. Then triethylamine (0.03mmol), resorcinol (0.8mmol), formaldehyde (0.8mol) and sodium carbonate (0.01mmol) were added and stirred continuously. Subsequently, 3.5g of the second precursor obtained in step S2 (2) was added. Then, polymerization was carried out at 90℃ for 10h, and then vacuum dried at 90℃ for 18h, and then the second carbon coating was carried out at 750℃ for 15h under nitrogen atmosphere. Finally, the silica layer was removed with 5wt% HF solution to obtain the third precursor. The third precursor includes tin-carbon composite particles; the tin-carbon composite particles have a core-shell structure, with an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first gap is distributed between the first carbon layer and the second carbon layer, the first carbon layer also includes nitrogen doping and porous tin oxide, and the second carbon layer also includes nitrogen doping.
[0188] S4, the third precursor prepared in step S3 is mixed with humic acid in a mass ratio of 100:15, and added into deionized water and mixed evenly, the solid-liquid ratio is controlled at 1:12, and then a 28wt% ammonia solution is added dropwise under stirring until the humic acid powder is completely dissolved, and then heated to 90°C and the solvent is evaporated to make the humic acid evenly coated on the surface of the third precursor; and sintered at 300°C for 10 hours in a microwave oven (microwave power of 1000W), cooled to room temperature, taken out, and then placed in a tubular furnace under an inert atmosphere at a rate of 3°C / min from room temperature to 700°C for 18 hours, so that the humic acid is thermally decomposed and graphene is synthesized in situ to obtain a tin-carbon composite material. The structure of the tin-carbon composite material includes tin-carbon composite particles and a graphene layer coated on the tin-carbon composite particles; the tin-carbon composite particles have a core-shell structure, with an inner core and a shell layer coating the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, a first gap is distributed between the first carbon layer and the second carbon layer, the first carbon layer also includes nitrogen doping and porous tin oxide, and the second carbon layer also includes nitrogen doping.
[0189] Effect Example 1
[0190] The tin-carbon composite material prepared in the embodiment of the present invention includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second gaps are distributed between the tin-carbon composite particles; a single tin-carbon composite particle has a core-shell structure, with a core and a shell coating the core; wherein the core includes porous tin oxide; the shell includes a first carbon layer and a second carbon layer in sequence along a direction away from the core, a first gap is distributed between the first carbon layer and the second carbon layer, the first carbon layer also includes nitrogen doping and porous tin oxide, and the second carbon layer also includes nitrogen doping.
[0191] The inductively coupled plasma (ICP) method is used to test the element content (tin, carbon, oxygen and nitrogen content) in the tin-carbon composite material prepared by the present invention. The test method is as follows: (1) Pre-treatment by microwave digestion method, 0.5g of the tin-carbon composite material prepared in the embodiment or the comparative example is placed in a digestion tank, 3mL of concentrated nitric acid and 9mL of concentrated sulfuric acid are added in sequence with a liquid adder, and the mixture is shaken well; and the mixture is kept at a constant temperature of 160°C for 3min, 180°C for 3min, 200°C for 10min, and 220°C for 10min, and then cooled to room temperature, filtered with quantitative filter paper, and the filtrate is placed in a 50mL volumetric flask as the test solution; (2) The above test solution is tested in the PerkinElmer ICP spectrometer Avio™ 200 device; the test condition is an air pressure of 2.5MPa.
[0192] The D50 of the tin-carbon composite materials prepared in the embodiment and the comparative example was tested using a Malvern particle size tester.
[0193] The conductivity was measured at room temperature using an Orion Star™ A212 conductivity benchtop meter.
[0194] The charge transfer resistance was measured by electrochemical impedance spectroscopy (compacted density 1.65 g / cm 3 )get.
[0195] The above physical and chemical results are shown in Table 1 below.
[0196] Table 1
[0197]
[0198] Note: The content of each element in the above table represents the percentage of the mass of each element in the total mass of the silicon-tin-carbon composite material.
[0199] Effect Example 2
[0200] The preparation method of the button cell used for testing the electrochemical performance is as follows: the tin-carbon composite material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a ratio of 95.5:1.5:1.5:1.5, and applied on a copper foil with a compaction density of 1.60 g / cm 3 , vacuum dried as the negative electrode, lithium metal as the counter electrode, the electrolyte using 1M LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) in a mass ratio of 1:1, the separator is PE / PP / PE composite film, and assembled into a button battery.
[0201] The above button cell was subjected to various electrical performance tests on a blue battery tester, the test condition was 25°C, and the charging voltage limit was 0.005-2V.
[0202] (1) First discharge specific capacity and first coulombic efficiency
[0203] The charge and discharge were carried out at a rate of 0.1C, and the first discharge specific capacity and the first coulombic efficiency were tested. The test results are shown in Table 2.
[0204] (2) Cycle performance
[0205] The charge and discharge cycles were performed 300 times at a rate of 0.1C, and the 300th discharge specific capacity was recorded as the 300-cycle retention capacity. The test results are shown in Table 2.
[0206] Table 2
[0207]
[0208] (3) Rate performance
[0209] The test conditions for rate performance are: rate charge and discharge at a current density of 0.1 mA / g-3 mA / g, and the charging voltage is limited to 0.005-2 V. The rate performance is tested at a current density of 0.1 mAh / g. The results are shown in Table 3.
[0210] Table 3
[0211]
[0212] As can be seen from Table 2 and Table 3, compared with Comparative Examples 1-4, Example 1-15 obtains a tin-carbon composite material by first carbon-coating porous tin oxide, then coating with silicon dioxide, preparing a cluster structure and carbon-coating, obtaining a cluster structure, and then coating with graphene. The tin-carbon composite material obtained in Example 1-14 includes a cluster structure and a graphene layer; the cluster structure includes a plurality of tin-carbon composite particles, and a single tin-carbon composite particle includes a porous tin oxide, a first carbon layer and a second carbon layer; the design of the porous structure, the multi-layer carbon layer and the cluster structure provides space for the expansion of the tin oxide particles, so that its expansion is effectively suppressed; further, the in-situ coating of graphene enhances the electrical conductivity and mechanical properties of the tin-carbon composite material, and further improves its volume expansion defect. Therefore, the tin-carbon composite material obtained in Example 1-14 has better first coulomb efficiency, cycle performance and rate performance than the tin-carbon composite material obtained in Comparative Examples 1-4.
Claims
1. A tin-carbon composite material, characterized in that: It includes a cluster structure and a graphene layer coated on the surface of the cluster structure; the cluster structure includes a plurality of tin-carbon composite particles, and second gaps are distributed between the tin-carbon composite particles; Among them, a single tin-carbon composite particle has a core-shell structure, which includes an inner core and a shell layer covering the inner core; wherein the inner core includes porous tin oxide; the shell layer includes a first carbon layer and a second carbon layer in sequence along a direction away from the inner core, and a first gap is distributed between the first carbon layer and the second carbon layer.
2. The tin-carbon composite material according to claim 1, characterized in that The tin-carbon composite material satisfies the following conditions A and / or B: A. In the single tin-carbon composite particle, the first carbon layer further comprises heteroatoms and / or tin-containing substances; preferably, the first carbon layer further comprises heteroatoms and tin-containing substances; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; Wherein, the tin-containing substance is preferably porous tin oxide; When the tin-containing substance is porous tin oxide, the porous tin oxide is preferably prepared by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12; The type of the inorganic tin source is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride; the molar ratio of the inorganic tin source to the base is preferably 1:(1.5-2.5), more preferably 1:(1.7-2.0), such as 1:1.8; the reaction temperature is preferably 50-90°C, such as 60-80°C; the reaction time is preferably 40-60min, such as 50min; B. In the single tin-carbon composite particle, the second carbon layer further includes heteroatoms; The heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen Among them, when the first carbon layer and / or the second carbon layer in the single tin-carbon composite particle includes heteroatoms, the content of heteroatoms is preferably 0.2%-1.0%, more preferably 0.6%-0.8%, for example 0.65%, 0.64%, 0.62%, 0.61%, 0.59%, 0.58%, 0.56%, 0.52%, 0.51% or 0.49%; the content of heteroatoms represents the percentage of the mass of heteroatoms to the mass of the tin-carbon composite material.
3. The tin-carbon composite material according to claim 1, characterized in that The tin-carbon composite material satisfies one or more of the following conditions AD: A. The D50 of the tin-carbon composite material is 250-400 nm, preferably 280-370 nm, for example 365, 355, 350, 340, 330, 320 or 300 nm; B. The tin content of the tin-carbon composite material is 40%-60%, preferably 45%-55%, for example 51.9%, 51.3%, 51.2%, 51.1%, 50.9%, 50.7%, 50.6%, 50.3%, 50.1% or 49.9%; C. The carbon content of the tin-carbon composite material is 30%-50%, preferably 35%-45%, for example 40.94%, 40.2%, 40.85%, 40.51%, 40.31%, 40.24%, 40.07%, 39.99%, 39.97%, 39.89%, 39.87%, 39.79% or 39.26%; D. The oxygen content of the tin-carbon composite material is 5%-10%, preferably 6%-9%, for example 8.42%, 8.37%, 8.32%, 8.27%, 8.21%, 8.19%, 8.17%, 8.14%, 8.03%, 8.01%, 7.99%, 7.98%, 7.97% or 7.84%; The content of each element mentioned above represents the percentage of the mass of each element to the mass of the tin-carbon composite material.
4. A method for preparing a tin-carbon composite material, characterized in that: It includes the following steps: S1, performing a first carbon coating on porous tin oxide to obtain a first precursor; S2, coating the first precursor with silicon dioxide to form a silicon dioxide layer to obtain a second precursor; The aqueous dispersion of the second precursor and the oil phase solution containing an emulsifier are mixed, the solvent is removed, and heat-treated to obtain a third precursor; S3, performing a second carbon coating on the third precursor, removing the silicon dioxide layer, and obtaining a fourth precursor; S4, coating the fourth precursor with graphene to obtain a tin-carbon composite material.
5. The method for preparing the tin-carbon composite material according to claim 4, characterized in that: The preparation method of the tin-carbon composite material meets one or more of the following conditions: In A and S1, the porous tin oxide is prepared by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12; The type of the inorganic tin source is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride; the molar ratio of the inorganic tin source to the base is preferably 1:(1.5-2.5), more preferably 1:(1.7-2.0), such as 1:1.8; the reaction temperature is preferably 50-90°C, such as 60-80°C; the reaction time is preferably 40-60min, such as 50min; B. In S1, the temperature of the first carbon coating is 550-850°C, such as 650, 700 or 750°C; In C and S1, the first carbon coating time is 6-15 hours, such as 8, 10 or 12 hours; D. In S1, the type of carbon source during the first carbon coating is phenolic resin and / or asphalt, such as phenolic resin fixed by a surfactant; In E and S1, the first carbon-coated carbon source further includes heteroatoms and / or tin-containing substances; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; when the type of the heteroatom is nitrogen, the type of the nitrogen source is preferably one or more of p-nitroaniline, nitroaniline, melamine, triethylamine, pyridine and azobis(ethylbutyronitrile), such as triethylamine; Wherein, the tin-containing substance is preferably porous tin oxide; the porous tin oxide is preferably prepared by the following steps: mixing an aqueous solution of an inorganic tin source and a base, reacting to obtain porous tin oxide; the pH of the system during the reaction is 5-12; The type of the inorganic tin source is preferably one or more of anhydrous tin chloride, stannous chloride and stannous sulfate, such as stannous chloride; the molar ratio of the inorganic tin source to the base is preferably 1:(1.5-2.5), more preferably 1:(1.7-2.0), such as 1:1.8; the reaction temperature is preferably 50-90°C, such as 60-80°C; the reaction time is preferably 40-60min, such as 50min; In F and S2, the preparation method of coating the first precursor with silicon dioxide comprises the following steps: mixing the first precursor, a silicon source and an ammonia solution, acid washing, and heat treating; Wherein, the type of the silicon source is preferably a silicate or a silicate; the silicate is preferably ethyl orthosilicate and / or methyl orthosilicate; the silicate is preferably one or more of sodium silicate, potassium silicate, magnesium silicate and iron silicate; the mass volume ratio of the first precursor to the silicon source is preferably (2-5) g: (3-10) mL, for example, 4 g: 8 mL or 5 g: 6 mL; the heat treatment temperature is preferably 600-800°C, for example, 600 or 650°C; the heat treatment time is preferably 6-10 h, for example, 8 h; the rate of heating from room temperature to the heat treatment temperature is preferably 1-10°C / min, for example, 3°C / min; In G and S2, the aqueous dispersion of the second precursor comprises a second precursor, a surfactant and water; Wherein, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; Wherein, the ratio of the second precursor, the surfactant and the water is preferably (3-5) g: (0.3-0.5) mol: 300 mL, for example 4 g: 0.45 mol: 300 mL; In H and S2, the type of the emulsifier is an emulsifier with a hydrophile-lipophile balance value of 3-8, preferably an emulsifier with a hydrophile-lipophile balance value of 4-7, and more preferably one or more of propylene glycol fatty acid ester, diethylene glycol monooleate, glyceryl monostearate and diethylene glycol monolaurate, such as diethylene glycol monooleate or glyceryl monostearate; In I and S2, the oil phase solvent in the oil phase solution containing the emulsifier is an olefin having 12 to 28 carbon atoms, such as 1-octadecene; In J and S2, the mass ratio of the second precursor to the emulsifier is 4:(0.9-2.4), for example, 4:1.8; In K and S2, the heat treatment temperature is 450-600°C, for example, 550°C; L. The heat treatment time is 0.5-1.5h, for example 1h.
6. The method for preparing the tin-carbon composite material according to claim 5, characterized in that: The preparation method of the tin-carbon composite material satisfies any one of the following conditions AE: In A and S1, when the type of carbon source during the first carbon coating is a phenolic resin, the method for preparing the porous tin oxide for the first carbon coating preferably comprises the following steps: mixing resorcinol, formaldehyde, a catalyst and the porous tin oxide, polymerizing and first carbon coating; Wherein, the molar ratio of the formaldehyde to the resorcinol is preferably (500-1000): (0.5-1.0), for example, 1000:1; the catalyst is preferably a base, more preferably sodium carbonate, sodium hydroxide or sodium citrate, such as sodium carbonate; the molar ratio of the resorcinol to the catalyst is preferably (0.5-1.0): (0.007-0.03), for example, 0.6: 0.01; the molar ratio of the resorcinol to the porous tin oxide is preferably (0.5-1.0): (2-3), for example, 0.6: 3 or 0.6: 2.5; the temperature of the polymerization reaction is preferably 80-100° C., for example, 90° C.; the time of the polymerization reaction is preferably 2-10 h, for example, 8 h; In B and S1, when the type of carbon source during the first carbon coating is a phenolic resin fixed with a surfactant, the method for preparing the porous tin oxide for the first carbon coating preferably comprises the following steps: mixing an aqueous solution of a surfactant, resorcinol, formaldehyde, a catalyst and the porous tin oxide, a polymerization reaction and a first carbon coating; The type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; the molar ratio of the surfactant to the resorcinol is preferably (0.3-0.65):(0.5-1.0), such as 0.45:0.6; In C and S1, when the carbon source also includes heteroatoms during the first carbon coating, the method for preparing the porous tin oxide by first carbon coating preferably includes the following steps: mixing the heteroatom source, resorcinol, formaldehyde, a catalyst and the porous tin oxide, polymerization reaction and first carbon coating; Wherein, the molar ratio of the heteroatom source to the resorcinol is preferably (0.01-0.09):(0.5-1.0), for example, 0.04:0.6; In D and S1, when the carbon source also includes a tin-containing substance during the first carbon coating, the method for preparing the porous tin oxide for the first carbon coating preferably includes the following steps: mixing an aqueous solution including a surfactant and a tin-containing substance, resorcinol, formaldehyde, a catalyst and the porous tin oxide, a polymerization reaction and a first carbon coating; Wherein, the type of the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride, hexadecyldimethylbenzylammonium bromide and dodecyldimethylbenzylammonium bromide, such as hexadecyltrimethylammonium bromide; the molar ratio of the surfactant to the tin-containing substance is preferably (0.3-0.65):(0.5-1.0) g, such as 0.45:0.5 or 0.45:0.8; the molar ratio of the tin-containing substance to the porous tin oxide is preferably (0.5-1.0):(2-3), such as 0.8:3, 0.5:3 or 0.8:2.5; In E and S1, when the carbon source also includes heteroatoms and tin-containing substances during the first carbon coating, the method for preparing the porous tin oxide for the first carbon coating preferably includes the following steps: mixing an aqueous solution including a surfactant and a tin-containing substance with a heteroatom source, resorcinol, formaldehyde, a catalyst and porous tin oxide, polymerization reaction and the first carbon coating.
7. The method for preparing the tin-carbon composite material according to claim 4, characterized in that: The preparation method of the tin-carbon composite material meets one or more of the following conditions AG: In A, S3, the temperature of the second carbon coating is 500-900°C, such as 700 or 750°C; In B and S3, the second carbon coating time is 8-24 hours, for example, 15 hours; In C and S3, the type of carbon source during the second carbon coating is phenolic resin and / or asphalt, such as phenolic resin fixed by a surfactant; D. In S3, the second carbon-coated carbon source further includes heteroatoms; Wherein, the type of the heteroatom is preferably one or more of phosphorus, boron, nitrogen and sulfur, such as nitrogen; In E and S4, the carbon source used in the graphene carbon coating is humic acid; Wherein, when the carbon source is humic acid, the graphene carbon coating is preferably performed by first mixing the fourth precursor, humic acid and water, and then dropping an ammonia solution under stirring conditions to remove the solvent; In F and S4, the mass ratio of the fourth precursor to the carbon source during the carbon coating of the graphene is 100:(10-20), preferably 100:(11-18), for example 100:15 or 100:12; In G and S4, the graphene carbon coating is subjected to a first-stage sintering, cooling and a second-stage sintering, and the temperature of the second-stage sintering is higher than the temperature of the first-stage sintering; The temperature of the first sintering step is preferably 200-350°C, such as 260 or 300°C; the time of the first sintering step is preferably 5-15h, such as 10h; the first sintering step is preferably carried out in a microwave oven; the power of the microwave oven is preferably 800-1100W, such as 1000W; Among them, the temperature of the second stage sintering is preferably 500-800°C, such as 600 or 700°C; the time of the second stage sintering is preferably 10-24h, such as 18h; the rate of heating from room temperature to the temperature of the second stage sintering is preferably 1-10°C / min, such as 3°C / min.
8. A tin-carbon composite material, characterized in that The tin-carbon composite material is prepared by the preparation method of any one of claims 4 to 7.
9. A pole piece, characterized in that: It comprises the tin-carbon composite material according to any one of claims 1 to 3 or claim 8.
10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 9.
Citation Information
Patent Citations
High-performance tin-carbon composite negative electrode material and preparation method thereof
CN116779825A